2020
DOI: 10.3892/etm.2020.8725
|View full text |Cite
|
Sign up to set email alerts
|

Loganin attenuates intestinal injury in severely burned rats by regulating the toll‑like receptor 4/NF‑κB signaling pathway

Abstract: Severe burns may lead to intestinal inflammation and oxidative stress, resulting in intestinal barrier damage and gut dysfunction. Loganin, an iridoid glycoside compound, has been isolated from Cornus officinalis Sieb. et Zucc; however, its role in the treatment of burn injury is yet to be fully elucidated. Therefore, the present study examined the effect of loganin administration on burn-induced intestinal inflammation and oxidative stress after severe burns in male Sprague-Dawley rats. Histological injury wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
(36 reference statements)
2
13
0
Order By: Relevance
“…2,10) According to our results, loganin strongly inhibited LPS-induced ROS formation in RAW264.7 macrophages. Although the antioxidant potential of loganin has been reported in previous studies, 18,25,26) the results of this study support the use of loganin as an antioxidant for the management of oxidative stress associated with inflammatory responses. Certain antioxidant signaling pathways negatively modulate excessive inflammatory responses to maintain homeostasis in the body.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…2,10) According to our results, loganin strongly inhibited LPS-induced ROS formation in RAW264.7 macrophages. Although the antioxidant potential of loganin has been reported in previous studies, 18,25,26) the results of this study support the use of loganin as an antioxidant for the management of oxidative stress associated with inflammatory responses. Certain antioxidant signaling pathways negatively modulate excessive inflammatory responses to maintain homeostasis in the body.…”
Section: Discussionsupporting
confidence: 61%
“…[14][15][16] A number of previous studies have shown that loganin has a variety of beneficial pharmacological effects, including anti-inflammatory, antioxidant, neuroprotective, immune regulatory and anti-tumor effects. [17][18][19][20][21][22][23][24] Recently, Cheng et al 25) reported that loganin can ameliorate pyroptosis, an inflammatory programmed cell death, by mitigating oxidative stress through inhibition of ROS generation and inactivation of NF-κB in high glucose-stimulated Schwann cells. In addition, it has been proposed that the effectiveness on anti-inflammation and antioxidant of loganin could be mediated by modulating the TLR4/NF-κB signaling pathway in an experimental model of loganine burn injury, 26) and the inhibition of TLR4/NF-κB activity was also attributed to suppress the inflammatory response upon LPS in the intestinal epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, loganin (131), loganic acid (132) and morroniside (136) are the compounds with more reported biological activities. Loganin has been proved with inhabitation effect on inflammatory response ( Wen et al, 2020 ; Wei et al, 2013a ) and mitigative effect on osteoarthritis ( Hu et al, 2020 ). Morroniside has shown protective effect against H 2 O 2 -induced damage in human neuroblastoma cells ( Zhong et al, 2017 ).…”
Section: Phytochemistrymentioning
confidence: 99%
“…Similarly, Shirin and colleagues revealed that acute administration of loganin could enhance spatial memory in diabetic rats (Babri et al, 2013). Moreover, Wen et al (2020) illustrated that loganin could ameliorate burn injuries and significantly reduce the production of inflammatory cytokines and oxidative stress by repressing the activation of the TLR4/NF-κB signaling pathway. To the best of our knowledge, only one study has implied that loganin appears to suppress the progression of atherosclerosis (Li et al, 2016).…”
Section: Discussionmentioning
confidence: 99%